Ecological Grief and Anxiety: The Voice of Native American in Joy Harjo’s Selected Poems - Astuti, Epata Puji; Iskarna, Tatang (Humanis, 2024)
The arrival of European colonizers led to the disruption of the nature and ecosystem. As the indigenous people with a close relationship to nature, Native Americans express their grief and anxiety about the condition of nature through literary work. The study presented in the present article aims to scrutinize three selected poems by Joy Harjo “Remember”, “Praise the Rain”, and “I am a Prayer” to see how the poet expresses her ecological grief and anxiety. The lines and stanzas of each poem are analyzed using the theory of intrinsic elements and the five stages of grief by Elisabeth Kubler-Ross. The researchers use a descriptive qualitative method and employ a psychological approach to reveal the speaker's suffering in the poem psychologically in which she feels grieved because of the loss of nature. The findings were that there were five stages of grief portrayed in the poems implicitly, that is, denial, anger, bargaining, depression, and acceptance. The speaker’s grief and anxiety can be seen from the personification, repetition, and imagery used in the poems. Joy Harjo offers a different way to experience the stage of ecological grief and anxiety. She invites us to honor the journey of grief with empathy, wisdom, and a profound appreciation for the natural world. Harjo invites a deeper awareness that is both accepting of past wounds and open to future possibilities. The acceptance of grief is a crucial step toward reconnection. It is only by accepting the grief of what has been lost that one can truly remember, appreciate, and care for what remains.